Pendampingan Pemasaran Criping Singkong Melalui Media Instagram - Andhita Risko Faristiana; Erica Lutvy Anindia Sary (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2024)
A community service program is one way of implementation to improve human resources (HR) 's ability to meet community needs and solve social problems together with the community to enhance social welfare per the vision, mission, and functions of Islamic state universities. Therefore, the author presents a cassava chip marketing innovation training program through Instagram media due to the impact of COVID-19 in Banyudono Village, Ponorogo as an effort to advance and improve the online market. Training for home industry owners using the ABCD (Asset Based Community Development) method which prioritizes assets and potential that exist around and are owned by the community. The main conclusions resulting from this service program, among others: First, this activity serves as an effort to improve the human resource capabilities of home industry owners related to the use of social media. Second, increasing insight and knowledge of home industry owners on the use of online marketing through Instagram social media in the era of globalization and the covid-19 pandemic.